Why did the chicken not cross the road? Anthropogenic development influences the movement of a grassland bird. Issue 3 (13th March 2022) - Londe, David W.; Elmore, Robert Dwayne; Davis, Craig A.; Hovick, Torre J.; Fuhlendorf, Samuel D.; Rutledge, Jimmy
Abstract: Movement and selection are inherently linked behaviors that form the foundation of a species' space‐use patterns. Anthropogenic development in natural ecosystems can result in a variety of behavioral responses that can involve changes in either movement (speed or direction of travel) or selection (resources used), which in turn may cause population‐level consequences including loss of landscape connectivity. Understanding how a species alters these different behaviors in response to human activity is essential for effective conservation. In this study, we investigated the effects of anthropogenic development such as roads, power lines and oil wells on the greater prairie‐chicken ( Tympanuchus cupido ) movement and selection behaviors in the post‐nesting and non‐breeding season. Our first objective was to assess using integrated step selection analysis (iSSA) if greater prairie‐chickens altered their movement behaviors or their selection patterns when encountering oil wells, power lines, or roads. Our second objective was to determine whether prairie‐chickens avoided crossing linear features such as roads or power lines by comparing the number of crossing events in greater prairie‐chicken movement tracks to the number of movements that crossed these features in simulated movement tracks. Based on the iSSA analysis, we found that greater prairie‐chickens avoided oil wells, power lines, and roads in both seasons, and altered their rate of movement when near anthropogenic structures. However, changes in speed varied by season, with prairie‐chickens increasing their movement rates in the post‐nesting season when near to development and decreasing movement rates in the non‐breeding season. Furthermore, prairie‐chickens crossed roads and power lines at much lower rates than expected. These changes in behavior can result in habitat loss for greater prairie‐chickens, as well as the potential loss of landscape connectivity. By considering both movement and selection, we were able to develop an ecological understanding of how increasing human activity may influence the space use of this species of conservation concern. Furthermore, this research provides insight into the decision‐making processes by animals when they encounter anthropogenic development.